2017
DOI: 10.2147/ott.s139639
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling pathway in colorectal cancer: function, mechanism, and therapy

Abstract: Colorectal cancer (CRC) is one of the most common gastrointestinal cancers worldwide. It is a complicated and often fatal cancer, and is related to a high disease-related mortality. Around 90% of mortalities are caused by the metastasis of CRC. Current treatment statistics shows a less than 5% 5-year survival for patients with metastatic disease. The development and metastasis of CRC involve multiple factors and mechanisms. The Hedgehog (Hh) signaling plays an important role in embryogenesis and somatic develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 113 publications
0
49
1
Order By: Relevance
“…Although the Notch and Hedgehog pathways have been shown in several studies to play a role in CRC development and progression, data are still contradictory and unclear (57). In our study, activation of the two examined pathways, as this is indicated by IHC overexpression of their components, did not result in significant associations in terms of outcome in early-stage CRC patients, with the exception of Notch3.…”
Section: Resultscontrasting
confidence: 63%
“…Although the Notch and Hedgehog pathways have been shown in several studies to play a role in CRC development and progression, data are still contradictory and unclear (57). In our study, activation of the two examined pathways, as this is indicated by IHC overexpression of their components, did not result in significant associations in terms of outcome in early-stage CRC patients, with the exception of Notch3.…”
Section: Resultscontrasting
confidence: 63%
“…Components of the hedgehog signaling pathway, such as SMO, Gli1, and Gli2, are deregulated in various cancers, and their expression levels are correlate with tumor progression and metastasis [14,22,29,30]. Aberrant activation of the hedgehog signaling pathway may promote colon cancer growth, recurrence, metastasis and stem cell survival and expansion [31,32]. Our study showed that when BEX2 was knocked out, the hedgehog signaling pathway could be activated.…”
Section: Discussionmentioning
confidence: 79%
“…Approximately 90% of colorectal cancer-related mortality is caused by tumor distant metastases [ 28 ]. Suppression of tumor invasion can effectively inhibit tumor cell spread and infiltration into distant organs.…”
Section: Discussionmentioning
confidence: 99%